Global analysis and development of a predictive tool of the effect of tube inclination on two-phase heat transfer: Boiling, condensation and heated gas-liquid flows. (5th November 2019) - Viscito, Luca; Lips, Stéphane; Revellin, Rémi
Highlights: Global analysis of the effect of channel orientation on two-phase heat transfer. 5408 data points collected from independent published works. Flow boiling, flow condensation and heated gas-liquid flows at various orientations. Inclination effect is correlated to the most influencing non-dimensional numbers. New tool to establish whether heat transfer might be affected by channel orientation. Abstract: The influence of gravity on two-phase heat transfer represents a challenge to the design and development of thermal systems in which the tubes can be oriented at different inclination angles. In this regard, the present study is based on a global analysis of the effect of the channel orientation on the two-phase heat transfer coefficient, which was performed by collecting 5408 data points from independent published works that include flow boiling, flow condensation and heated gas-liquid flows at various orientations with respect to the gravity force. A comparison against existing prediction methods for two-phase heat transfer including the tube orientation effect has shown a very poor agreement, and no general tool is available in the literature to determine whether the effect of gravity is negligible or of major importance for specific applications. For these reasons, a new prediction tool is proposed. The Inclination effect Ih is defined as the maximum expected variation of the heat transfer coefficient when the tube inclination angle is changed, with respect to the predicted value in a horizontal arrangement. Using an unconstrained nonlinear optimization, the Inclination effect is correlated with the most influencing nondimensional groups of parameters for boiling and condensation heat transfer, providing satisfactory agreement with the experimental data ( MAE = 17.6% and 19.3%, respectively). The Ih is found to be a decreasing function of the vapor quality and mass flux, and it increases with larger diameters and alongside heat flux in flow boiling. This new tool can be employed in the design process of condensing and evaporating units, since it is able to establish whether the heat transfer coefficient might be affected by the channel orientation or, instead, a typical correlation for non-inclined tubes can be used.